Birt-Hogg-Dubé syndrome: a large single family cohort. Issue 1 (December 2016) - Skolnik, Kate; Tsai, Willis; Dornan, Kimberly; Perrier, Renée; Burrowes, Paul; Davidson, Warren
Abstract Background Birt-Hogg-Dubé (BHD) syndrome is an autosomal dominant condition characterized by dermatologic lesions, pulmonary manifestations, and renal tumors. The syndrome arises from germline mutations in the folliculin(FLCN) gene. We present findings from the single largest family BHD cohort described to date. Primary objectives were to characterize cystic lung changes on computed tomography (CT) chest scanning and identify features that stratify patients at higher risk of pneumothorax. Secondary objectives entailed description of the following: type and natural history of BHD-associated pneumothorax, pulmonary function characteristics, and relationship between cystic lung changes and pulmonary function. Methods The study was a retrospective chart review for a case series of a single family. Over 70 family members of a proband with documented BHD were identified, 68 of which consented to genetic testing. All those with confirmed BHD were offered a clinical assessment by the Medical Genetics and Pulmonary services which included a history, physical exam, complete pulmonary function tests, and computed tomography (CT) scan of the chest and abdomen. Results Thirty-six individuals had a heterozygous mutation in theFLCN gene (c.59delT). Of these, 100 % (28/28) had pulmonary cysts, 41 % (13/32) had spontaneous pneumothoraces, 26 % (8/31) had kidney cysts, 3 % (1/31) had renal tumors, and 53 % (18/34) had dermatologic manifestations. Recurrent pneumothoraces were common (40 %). Cyst size (OR 3.23, 95 % CI 1.35–7.73) and extent of lower lung zone disease (OR 6.43, 95 % CI 1.41–29.2) were the only findings associated with pneumothorax. The size or extent of cystic disease did not correlate with lung function results. Conclusions This is the largest single family cohort of patients with BHD syndrome documented to date. We found that all individuals had pulmonary cysts, pneumothoraces were common, and cyst size and lower lobe predominant disease were associated with pneumothorax. Lung function was generally preserved and not affected by a high cyst burden.